HUBUNGAN LOCUS OF CONTROL DENGAN PROBLEM FOCUSEDCOPING PADA MAHASISWA JURUSAN PENDIDIKAN GEOGRAFI UNIVERSITAS SYIAH KUALA - Amirda, Nurul Fitri; Zalmita, Novia; Purnomowati, Dyah Rahmani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
Students who take the thesis are required to be able to complete the thesis on time. In the drafting process students experience obstacles that cause these students to experience stress, so a coping strategy is needed to be able to solve these problems. Problem focused coping allows someone to plan or take action, and be ready to face all possibilities of the plan, so that the problems encountered can be solved. Factors that influence problem focused coping are personality characteristics including locus of control. This study aims to determine the relationship between locus of control and problem focused coping in students of the Geography Education Department at Syiah Kuala University. This study uses a quantitative approach and a type of correlational research. The population in this study were 62 students at the end of the Department of Geography Education at Syiah Kuala University. The sampling technique is the total population or total sampling. The data collection technique used in this study was a questionnaire. Data analysis techniques using simple correlation. Based on the results of statistical analysis it is known that the relationship between locus of control and problem focused coping is obtained by a simple regression equation Y = 92,27 + 0,22X which means that the independent variable has a positive influence on the dependent variable. The correlation coefficient of locus of control with problem focused coping is 0.18 which is very low, and the coefficient of determination () = 3,24%. The results of the significance test showed Fcount (2.16) Ftable (3.99) at a significance level of 5%, so H0 was accepted, meaning that there was no significant relationship between locus of control and problem focused coping in students of the Geography Education Department at Syiah Kuala UniveKeywords: Relationship, Locus of Control, Problem Focused Coping